Use of Conceptual Metaphors in Miguna Miguna’s Political Commentaries on Facebook in Kenya: A Conceptual Metaphor Perspective - WAHOME, MAINA; Nurhayati, Nurhayati (PAROLE: Journal of Linguistics and Education, 2023)
This paper examines Miguna's political commentaries on Facebook, which have become a potent force in Kenya's socio-political discourse. Known for his incisive and metaphor-laden commentaries, Miguna, popularly called "Double M", has sparked a surge in online political discussions, evoking both admiration and ire from the public. However, his style has also raised concerns about slander and libel in pursuing justice, secularism, and democracy. The gap in this study lies in the limited understanding of how conceptual metaphors, as utilized in Miguna's political commentaries on Facebook in Kenya, impact power structures, government policies, and communication practices. The study uses the Conceptual Metaphor Theory (CMT) by (Lakoff and Johnson, 1980) and the Deconstruction Theory (Derrida, 1967) to analyze the data collected from Miguna's Facebook page using a web scrapping tool, Octoparse. The Metaphor Identification Procedure Vrije Universiteit (MIPVU) was utilized to identify the conceptual metaphors in Miguna's commentaries. The analysis revealed seven metaphorical conceptualizations of politicians: despots, conmen and cartels, orphans and cows, corruption monsters, socialite bimbos, and human rights violators, with politicians as the source domains and despots, conmen and cartels, orphans and cows, corruption monsters, socialite bimbos, and human rights violators as the target domains. This study shows how metaphors contribute to political commentary, their impact on power structures, and their relevance in the digital age, specifically in Kenya. The findings have broader implications for freedom of speech, defamation, and responsible communication, guiding policymakers, educators, and media practitioners.